Sounding the Arctic in Chantal Bilodeau’s Climate Change Plays - Balestrini, Nassim W. (Nordic Theatre Studies, 2020)
Quebec-born playwright Chantal Bilodeau has been responding to the challenges of dramatizing anthropogenic climate change by developing an eight-part Arctic Cycle, each play of which is set in one of the nations that claims Arctic territory. Sila (2014) immerses audiences into a complex network of humans, animals, and mythical beings crisscrossing the Canadian Arctic. These movements circle around the Inuit concept of sila, which is the life-giving force of breath and voice. Thus, the sonic world of Sila focuses on voices speaking words, on performance poetry, and on the sounds of breath and wind. Bilodeau’ s second Arctic Cycle play, Forward (2016), addresses the long-term impact of Fridtjof Nansen’s polar exploration of the 1890s on Norway’s economy and society. In terms of sound, Forward features multiple musical performances rangingfrom traditional songs to European opera arias and Lieder to contemporary Norwegian electro-pop. The sonic features of both plays stress interdependence across time, space, as well as (non-)human, earthly, and metaphysical realms. Sila and Forward address climate change in a non-universalizing manner which promotes a heterarchical (rather than hierarchical) aesthetic fit for a growing awareness of planetary relationality.
Keywords: Theory and practice

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound